PreLab_10 - 1 B’ 1 S 1 =((A(AB)’)’. (B(AB)’)’)’...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Sarah Karam Friday 4 January 2008 200702037 Pre-Lab 10 S 1 = 1 1 1 1 B A B A + Let’s prove that the equation above can give: S 1 = 1 1 1 1 B A B A + Using Boolean algebra: S 1 = A(A+B).B(A+B) where A’ is equal to not A S 1 =A’ 1 B 1 + A
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 1 B’ 1 S 1 =((A(AB)’)’. (B(AB)’)’)’ S 1 =((A(A’+B’))’. (B(A’+B’))’)’ S 1 =((AB’)’(A’B)’)’ S 1 =(A’+B)’+(A+B’)’ S 1 =AB’+BA’...
View Full Document

This note was uploaded on 02/07/2011 for the course EECE 312L taught by Professor Ghassandeeb during the Fall '07 term at American University of Beirut.

Ask a homework question - tutors are online